Working through negativity: The influence of affective states on effort-based decision-making. (February 2023) - Byrne, Kaileigh A.; Liu, Yizhou; Shreeves, Michael; Six, Stephanie G.
Abstract: Affective states can influence a range of cognitive outcomes, such as decision-making. However, the effect of valence and arousal state inductions on effort-based decision-making is unclear. This study employed a mixed design in which all participants viewed low and high-arousal images, and participants were randomized to either a neutral, positive, or negative valence image manipulation. Participants repeatedly viewed a valenced-image and then completed a trial of the Effort Expenditure for Rewards Task (EFfRT). Results of Experiment 1 ( N  = 197) demonstrated that a valence induction manipulation influenced effort-based decision-making. Individuals in the negative valence condition chose fewer high-effort, difficult options than those in the neutral and positive valence conditions. Experiment 2 ( N  = 226) sought to explore the interplay between affective states and motivation on effort-based decision-making. Results of Experiment 2 replicated the finding that negative affective states impair willingness to engage in effortful tasks and showed that negative affect moderated the relationship between intrinsic motivation and willingness to exert effort. Self-reported arousal ratings, but not valence ratings, were also predictive of effort-based decisions. This work demonstrates that affective states may alter the cost of effort expenditure for potential rewards. Negative valence weakens one's volition to exert physical effort to obtain a monetary reward. Highlights: This study sought to examine the effect of valence and arousal on effort-based decision-making. Two experiments showed that negative valence led to decreased effort expenditure for rewards. This work shows that valence influences willingness to exert effort for rewards.